2012
DOI: 10.1111/j.1440-1819.2012.02325.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight in schizophrenia: From conceptualization to neuroscience

Abstract: Lack of insight into illness is a prevalent and distinguishing feature of schizophrenia, which has a complex history and has been given a variety of definitions. Currently, insight is measured and treated as a multidimensional phenomenon, because it is believed to result from psychological, neuropsychological and organic factors. Thus, schizophrenia patients may display dramatic disorders including demoralization, depression and a higher risk of suicide, all of which are directly or indirectly related to a lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 159 publications
(315 reference statements)
0
17
0
2
Order By: Relevance
“…More specifically, increased self-reflection is positively correlated with awareness of delusions and negatively with delusion severity (Engh et al, 2010). Additionally, a positive relationship between delusion severity and self-certainty has been consistently reported (Warman et al, 2007;Engh et al, 2010;Ouzir et al, 2012). These studies demonstrate evidence of both overlap and distinctiveness between clinical and cognitive insight and this might have clinical implications (Beck et al, 2011;Pijnenborg et al, 2011;Pijnenborg et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…More specifically, increased self-reflection is positively correlated with awareness of delusions and negatively with delusion severity (Engh et al, 2010). Additionally, a positive relationship between delusion severity and self-certainty has been consistently reported (Warman et al, 2007;Engh et al, 2010;Ouzir et al, 2012). These studies demonstrate evidence of both overlap and distinctiveness between clinical and cognitive insight and this might have clinical implications (Beck et al, 2011;Pijnenborg et al, 2011;Pijnenborg et al, 2014).…”
Section: Introductionmentioning
confidence: 82%
“…A fourth area of potential research includes future investigations that serve to elucidate how brain structure and function impact insight, as investigations into this could be informative for developing both advances into etiological theory and novel therapeutic approaches. To date, imaging studies suggest that a number of areas and anomalies may subserve impaired insight, including reduced total brain volume, ventricular enlargement, frontal lobe atrophy, reduced frontal volume, gray matter deficits in the cingulate, precuneus, temporal and parietal lobes [68]. However, continued research is needed for replication as well as to clarify how these abnormalities fit together and manifest clinically as impaired insight.…”
Section: Five Year Viewmentioning
confidence: 99%
“…Several studies have indeed suggested that a lack of insight in schizophrenia spectrum disorders is related to aberrant structure and function of the frontocortical systems (see [68] for detailed review). Abnormalities related to insight in schizophrenia include reduced total brain volume, ventricular enlargement, frontal lobe atrophy, reduced frontal volume, and gray matter deficits in the cingulate, precuneus, temporal, and parietal lobes [68].…”
Section: Neurocognition and Anomalous Brain Structure And Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many decades, poor insight has been considered a prevalent feature in patients diagnosed with chronic psychotic disorders 1 . The vast majority of scientific literature has defined insight as a multidimensional concept that includes awareness of a mental illness, recognition of the need for medication, awareness of the social consequences, and awareness of the presence of psychotic symptoms and the attribution of symptoms to the illness 2 .…”
Section: Introductionmentioning
confidence: 99%